Influence of Zn/Fe molar ratio on optical and magnetic properties of ZnO and ZnFe2O4 nanocrystal as calcined products of layered double hydroxides - Ali Ahmed, Abdullah Ahmed; Talib, Zainal Abidin; Hussein, Mohd Zobir; Flaifel, Moayad Husein; Al-Hada, Naif Mohammed (Hindawi Publishing Corporation, 2014)
The coprecipitation method has been used to synthesize layered double hydroxide (Zn-Fe-LDH) nanostructure at different Zn2+/Fe3+ molar ratios. The structural properties of samples were studied using powder X-ray diffraction (PXRD). LDH samples were calcined at 600°C to produce mixed oxides (ZnO and ZnFe2O4). The crystallite size of mixed oxide was found in the nanometer scale (18.1 nm for ZnFe2O4 and 43.3 nm for ZnO). The photocatalytic activity of the calcination products was investigated using ultraviolet-visible-near infrared (UV-VIS-NIR) diffuse reflectance spectroscopy. The magnetic properties of calcined LDHs were investigated using a vibrating sample magnetometer (VSM). The calcined samples showed a paramagnetic behavior for all Zn2+/Fe3+ molar ratios. The effect of molar ratio on magnetic susceptibility of the calcined samples was also studied.